Desenvolvimento de eletrodos modificados com polímeros condutores e nanotubos de carbono e aplicação na determinação de analitos de interesse farmacêutico em amostras biológicas e em fármacos - Troiani, Estela de Pieri (Universidade Federal de São Carlos, 2011)
In this work is reported the studies carried out modified electrodes with poly(1-aminoanthracene) (PAA) and poly(1-aminoanthraquinone) (PAAQ), and composite films from a mixture of polymers with carbon nanotubes (CNTs). These electrodes were used for determination of dopamine (DA), ascorbic acid (AA) and uric acid (UA) in synthetic and real biological samples; in addition, we performed the determination of norepinephrine (NE) and hydroquinone (HQ) in pharmaceutical samples. In this context, was evaluated the influence of a cathodic pretreatment applied to the modified electrodes by verifying a change in electrochemical properties of the films so that after pretreatment of the PAA electrode showed electrocatalytic response to DA while the PAAQ electrode showed a significant increase in DA response. In this work, PAA and PAAQ films were electropolymerized on platinum electrodes, and their surfaces were characterized by microscopic techniques. PAA film showed DA response only after the cathodic pretreatment, which consisted of applying a potential of −0.7 V for 3 s prior to voltammetric measurements. It was found that the union of CNT, PAA and cathodic pretreatment provided a positive synergy, resolving the overlapping oxidation peaks of DA, AA and UA in three well defined peaks. For the PAAQ film, simultaneous responses of AA, DA and UA, with well-defined oxidation peaks was obtained after application of pretreatment, not requiring the incorporation of CNTs in polymer matrix. Using differential voltammetry, analytical curve for AA, DA and UA were constructed with the composite electrode PAACNT showed detection limits of 39.5, 0.29 e 42.2 μmol L−1, respectively. To the cathodically pretreated PAAQ electrode, detection limits obtained were 25.0, 3.05, e 11.5 μmol L−1 for AA, DA and UA, respectively. xxvi Addition of the CNTs in PAAQ film provided a small increase in DA detection limit in the ternary mixture AA, DA and UA, with a value of 3.23 μmol L−1. Following a procedure was developed for NE analysis, using the square wave voltammetry technique (SWV) and using modified PAA electrode. The analytical curve was linear over the NE concentration range between 2.18 99.6 μmol L−1, with a detection limit of 0.58 μmol L−1. Finally, a procedure was developed for the HQ determination using the modified PAAQ electrode and SWV technique. Under optimized experimental conditions, analytical curve was constructed, the HQ concentration obtained range between 2.97 25.5×10−5 mol L−1 and detection limit equal 2.11 μmol L−1. The proposed methods were applied in biological and pharmaceutical samples, obtaining satisfactory results.
Development of modified electrodes with conducting polymers and carbon nanotubes to application in the determination of analytes of pharmaceutical interest in biological and drugs samples
Keywords: Química analítica; Eletrodos modificados; Polímeros condutores; Nanotubos de carbono; Métodos eletroanalíticos; CatecolaminasI; CIENCIAS EXATAS E DA TERRA::QUIMICA